Relations between terms: a cognitive approach. The interaction between Terminology, Lexicology, Translation Studies and translation practice - Thelen, Marcel (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper discusses two problem areas of Terminology: the word-term dis-tinction and a particular type of terminological relation, viz. the complex or associative relation. Both areas will be discussed in the light of the actual practice of translating and the translator. It will be argued that for the trans-lator to deal with these areas successfully there should be a contribution from basic translation practices and Translation Studies, on the one hand, and from Lexicology, notably TCM (“Two-Cycle Model of Grammar”), on the other.